2018
DOI: 10.1186/s41927-018-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of first-degree relatives of patients with rheumatoid arthritis about lifestyle modifications and pharmacological interventions to reduce the risk of rheumatoid arthritis development: a qualitative interview study

Abstract: Background There is increasing interest in the identification of people at risk of rheumatoid arthritis (RA) to monitor the emergence of early symptoms (and thus allow early therapy), offer lifestyle advice to reduce the impact of environmental risk factors and potentially offer preventive pharmacological treatment for those at high risk. Close biological relatives of people with RA are at an increased risk of developing RA and are therefore potential candidates for research studies, screening ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 36 publications
5
39
0
Order By: Relevance
“…Disease risk perception, ethical views on cohort participation, and willingness to change lifestyle to decrease disease risk are similar between individuals at risk of RA or axSpA. The previously reported high willingness of FDRs of RA patients to change their lifestyle [13][14][15] is also observed in the present at-risk populations. The willingness to use preventive medication seems higher in symptomatic RA-risk individuals compared to asymptomatic FDRs.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Disease risk perception, ethical views on cohort participation, and willingness to change lifestyle to decrease disease risk are similar between individuals at risk of RA or axSpA. The previously reported high willingness of FDRs of RA patients to change their lifestyle [13][14][15] is also observed in the present at-risk populations. The willingness to use preventive medication seems higher in symptomatic RA-risk individuals compared to asymptomatic FDRs.…”
Section: Discussionsupporting
confidence: 58%
“…However, information about perceptions of individuals at risk of RA regarding preventive treatment is still limited. Previous studies in first-degree relatives (FDRs) of RA patients showed that many were willing to make lifestyle changes such as weight loss or diet changes and that their willingness to start preventive medication was primarily influenced by perceived risk of RA development, medication effectiveness, and potential side effects [ 13 15 ]. Furthermore, the opinion of the health care professional might be an important attribute involved in the patient’s decision whether or not to take preventive treatment [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although they had developed strategies to cope with this situation, they indicated that they would have preferred additional tailored information and support at the time when they were told that they had an elevated risk of developing RA. Clinicians should address the information and support needs identified in the current study by further developing effective, tailored education to support decision‐making about whether to take a predictive test and to provide guidance and support for understanding and coping with test results .…”
Section: Discussionmentioning
confidence: 99%
“…63 However, discussions in that study suggested that lifestyle change, for example smoking cessation, was of limited interest. 63 Fear of drug side effects was highlighted as a central theme, which has also been identified in qualitative studies in Europe 58,60 .…”
Section: Reliable Access To First Degree Relatives Is Usually Indirecmentioning
confidence: 97%
“…It is therefore important to understand patients' perspectives in this context to identify barriers and facilitators to approaches targeting first-degree relatives. This was the focus of a UK based qualitative study 52 Preferences for interventions to reduce risk of developing RA Several European qualitative studies have explored preferences relating to preventive interventions for RA of first-degree relatives [58][59][60] , RA patients 52,59 , and ACPA positive individuals without arthritis. 53 Lifestyle change was preferred over pharmacological interventions to reduce RA risk 52, 53, 58-60 , however positive viewpoints were associated with the perspective that any intervention would need to substantially reduce or completely remove their risk of RA.…”
Section: Reliable Access To First Degree Relatives Is Usually Indirecmentioning
confidence: 99%